Comprehensive Profiling of Inflammatory Factors Revealed That Growth Differentiation Factor-15 Is an Indicator of Disease Severity in COVID-19 Patients - Teng, Xiangyun; Zhang, Jiaqi; Shi, Yaling; Liu, Yuntao; Yang, Yanqing; He, Jinyong; Luo, Shuhong; Huang, Yile; Liu, Yanxia; Liu, Dongdong; Li, Yizhe; Zhang, Shuangzhe; et al. (Frontiers in Immunology, 2021)
To systematically explore the biomarker which can predict the severity in COVID-19 patients and prevent the occurrence or development of severity in COVID-19 patients, the level of 440 severity associated factors were analyzed in asymptomatic, mild, moderate, severe, convalescent and healthy control group (categorized according to COVID-19 disease severity) groups. Factor candidates were validated by ELISA and functional relevance was uncovered by bioinformatics analysis. To identify the biomarker during the occurrence or development of COVID-19, patient sera from three different severity groups (moderate, severe, critical) at three time points (admission, remission, and discharge) were collected to measure the level of indicator candidates. Eleven differential cytokines associated with disease severity were pinpointed from 111 patients with different severity, the dynamic changes of GDF-15 reflect the progression of the disease, while the other factors include TRAIL R1, IGFBP-1, IGFBP-4, VCAM-1, sFRP-3, FABP2, Transferrin, GDF-15, IL-1 F7, IL-5 Ra, CD200. Elevation of white blood cell count, neutrophil count, Neutrophil-Lymphocyte Ratio (NLR), Alanine aminotransferase and Aspartate aminotransferase, low lymphocyte and eosinophil counts in the severe group were associated with the severity of COVID-19. GDF15 levels were observed to be associated with the severity of COVID-19 and the dynamic change of GDF15 levels was closely associated with the disease progression of COVID-19. Therefore, GDF15 might serve as an indicator of disease severity in COVID-19 patients.